Endocrine Autoimmunity in Pregnancy - Świątkowska-Stodulska, Renata; Berlińska, Agata; Stefańska, Katarzyna; Zieliński, Maciej; Kwiatkowski, Sebastian; Połom, Joanna; Andrysiak-Mamos, Elżbieta; Wydra, Piotr; Sworczak, Krzysztof (Frontiers in Immunology, 2022)
Human gestation leads to a number of physiological alterations which peak at the development of placenta known for, among many other functions, being a transient but highly potent endocrine organ. Hormonal activity of placenta is marked by its ability to continuously produce and secrete high levels of progesterone. Progesterone guards the well-being of the fetoplacental unit throughout the gestation and one of the proposed mechanisms of this principle involves the development of local and systemic immune tolerance mainly due to impediment of CD4+ lymphocytes activation. However, though these alterations are present and well-established, autoimmunity is not entirely rare and a wide spectrum of diseases can continue, or develop de novo, throughout the gestation or even after the delivery. Up-to-date data supports the existence of a relationship between the clinical course of chosen autoimmune diseases and levels of circulating progesterone. The most common autoimmune endocrinopathies in pregnant women are: Hashimoto’s disease, Graves’ disease, and, more rarely, primary adrenal insufficiency. Gestation can influence the clinical course of these endocrinopathies in patients who were diagnosed before conception. Multiple particles, like TSH-receptor stimulating antibodies, thyroid hormones, glucocorticoids, and anti-thyroid medications, can cross the placental barrier and evoke biological action in fetal tissues. Thyroid pathology in the form of postpartum thyroiditis is particularly prevalent in patients with positive anti-thyroperoxidase and anti-thyroglobulin antibodies. In our paper, we would like to address physiological, physiopathological, and clinical aspects of endocrine autoimmunity throughout human gestation, as well as special circumstances to consider in pregnant women.